Nabye aftrede: Predikante se belewing van hul gemeente, persoonlike welstand en finansies - Alsemgeest, Liezel (Stellenbosch theological journal, 2016)
Imminent retirement: Pastors’ experience of their congregation, personal well-being and financesThe provisions of pastors to congregations is of great importance to the Dutch Reformed Church and its congregation. To retire is a complex process of transition affecting various aspects - among others psychological, spiritual and financial aspects. According to current estimates, more than half of the full-time pastors in the Dutch Reformed Church could retire within the next fifteen years. A quantitative online survey was conducted amongst pastors who will retire in the near future, their experience of their congregation, personal well-being and financial prospects before and during retirement was taken into account. For the first time research provides insight into what will happen in churches when a pastor retires. The information should provide valid conclusions and recommendations can be made regarding the demand for pastors (and students?) in order to plan for effective ministry within churches.